Like/Dislike Prediction for Sport Shoes With Electroencephalography: An Application of Neuromarketing - Zeng, Li; Lin, Mengsi; Xiao, Keyang; Wang, Jigan; Zhou, Hui (Frontiers in Human Neuroscience, 2022)
Neuromarketing is an emerging disciplinary domain for prospective businesses on consumer preference. Consumer preference prediction based on EEG can reliably predict likes/dislikes of a product. However, the current EEG prediction and classification accuracy have yet to reach ideal level. In addition, it is still unclear how different brain region information and different features such as PSD and brain asymmetry affect the prediction accuracy. Our study shows that by taking footwear products as an example, the recognition accuracy of product likes/dislikes reaches 91.32%. Compared with other brain regions, the features of the frontal brain region obtained a higher prediction accuracy, but the fusion of the features of the whole brain region could improve the prediction accuracy of likes/dislikes even further. Based on the PSD features of all channels, a classification accuracy of 88.85 % was attained, whereas prediction accuracy of 82.04% was obtained based on the brain asymmetry features of all symmetrical EEG channels. Future work would be done to correlate the EEG based prediction results with product sales and self-reports.